Silent T1 mapping using the variable flip angle method with B1 correction. Issue 2 (21st January 2020) - Ljungberg, Emil; Wood, Tobias; Solana, Ana Beatriz; Kolind, Shannon; Williams, Steven C. R.; Wiesinger, Florian; Barker, Gareth J.
Abstract : Purpose: To compare the silent rotating ultrafast imaging sequence (RUFIS) to a traditional Cartesian spoiled gradient‐echo (SPGR) acquisition scheme for variable flip angle (VFA) T 1 mapping. Methods: A two‐point VFA measurement was performed using RUFIS and Cartesian SPGR in a quantitative phantom and healthy volunteers. To correct for B 1 errors, a novel silent magnetization prepared B 1 map acquisition (SIMBA) was developed, which combined with RUFIS VFA allows for a completely silent T 1 mapping protocol. Results: The silent protocol was found to have comparable repeatability but higher reproducibility in vivo compared to the standard SPGR protocol, and showed no increase in acoustic noise levels above background noise levels compared to a 33 dBA increase for the SPGR acquisition. Conclusions: VFA T 1 mapping using RUFIS is a feasible alternative to SPGR, achieving silent T 1 mapping with comparable acquisition time.